Traction-assisted endoscopic submucosal dissection for resection of ileocecal valve neoplasia: a French retrospective multicenter case series - Yzet, Clara; Wallenhorst, Timothée; Jacques, Jérémie; Figueiredo Ferreira, Mariana; Rivory, Jérôme; Rostain, Florian; Masgnaux, Louis-Jean; Grimaldi, Jean; Legros, Romain; Lafeuille, Pierre; Albouys, Jérémie; Subtil, Fabien; Schaefer, Marion; Pioche, Mathieu (Endoscopy, 2024)
Background The ileocecal valve (ICV) is considered to be one of the most difficult locations for endoscopic submucosal dissection (ESD). The objective of this study was to evaluate the efficacy and safety of traction-assisted ESD in this situation.Methods All patients who underwent traction-assisted ESD for an ICV lesion at three centers were identified from a prospective ESD database. En bloc and R0 rates were evaluated. Factors associated with non-R0 resection were explored.Results 106 patients with an ICV lesion were included. The median lesion size was 50 mm (interquartile range 38–60) and 58.5% (62/106) invaded the terminal ileum. The en bloc and R0 resection rates were 94.3% and 76.4%, respectively. Factors associated with non-R0 resection were lesions covering ≥75% of the ICV (odds ratio [OR] 0.21. 95%CI 0.06–0.76; P=0.02), and involving the anal lip (OR 0.36, 95%CI 0.13–0.99; P=0.04) or more than two sites on the ICV (OR 0.27, 95%CI 0.07–0.99; P=0.03).Conclusion Traction-assisted ESD for treatment of ICV lesions was a safe and feasible option. Large lesions and anal lip involvement appeared to be factors predictive of difficulty.